2018
DOI: 10.1097/md.0000000000010631
|View full text |Cite
|
Sign up to set email alerts
|

Chronic constipation

Abstract: Background:Chronic constipation is described as a common complication determined by difficult and/or rare passage of stool or both. The difference in definition of constipation has led to a wide range of reported prevalence (i.e., between 1% and 80%). Various factors are involved in the pathogenesis of the disease, including type of diet, genetic predisposition, colonic motility, absorption, social economic status, daily behaviors, and biological and pharmaceutical factors. Diagnostic and therapeutic options p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
150
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(168 citation statements)
references
References 75 publications
2
150
0
16
Order By: Relevance
“…Constipation is a more common bowel disease in adults. The symptoms of constipation include dry stool or difficulty passing stool [1]. Although constipation is not fatal, long-term abdominal uncomfortable condition lowers life quality of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constipation is a more common bowel disease in adults. The symptoms of constipation include dry stool or difficulty passing stool [1]. Although constipation is not fatal, long-term abdominal uncomfortable condition lowers life quality of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Diet therapy is another method for treating constipation. Several studies have indicated that a high-fiber diet can increase stool excretion and shorten colon transit time, while poor-fiber diet induces constipation [1]. Soluble-fiber-enriched foodstuffs, such as psyllium, are proved to be beneficial for constipation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Different factors can contribute to this, including diet, lifestyle and medications [7]. Constipation can also signal the presence of other underlying disorders such as diabetes, coeliac disease and cancer [8].A recent review estimated the average prevalence of constipation at 16% worldwide [9]. In the United States, the number of hospital emergency visits linked to constipation increased by 41.5% between 2006 and 2011 [10].…”
mentioning
confidence: 99%
“…In the United States, the number of hospital emergency visits linked to constipation increased by 41.5% between 2006 and 2011 [10]. Constipation is thought to be twice as common in women than in men [9]. Women at the postpartum stage (several weeks after pregnancy) are often affected by the condition, with up to 25% of women reporting the incidence of constipation [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation